Surface-engineered quantum dots/electrospun nanofibers as a networked fluorescence aptasensing platform toward biomarkers. Issue 43 (30th October 2017) - Yang, Tong; Hou, Peng; Zheng, Lin Ling; Zhan, Lei; Gao, Peng Fei; Li, Yuan Fang; Huang, Cheng Zhi
Abstract : QD-lit and networked electrospun nanofibrous membranes were employed as an aptasensor to facilely, sensitively and specifically detect biomarkers based on NSET between QDs and AuNPs. Abstract : A membrane-based fluorescent sensing platform is a facile, point-of-care and promising technique in chemo/bio-analytical fields. However, the existing fluorescence sensing films for cancer biomarkers have several problems, with dissatisfactory sensitivity and selectivity, low utilization of probes encapsulated in films as well as the tedious design of membrane structures. In this work, a novel fluorescence sensing platform is fabricated by bio-grafting quantum dots (QDs) onto the surface of electrospun nanofibers (NFs). The aptamer integrated into the QDs/NFs can result in high specificity for recognizing and capturing biomarkers. Partially complementary DNA-attached gold nanoparticles (AuNPs) are employed to efficiently hybridize with the remaining aptamer to quench the fluorescence of QDs by nanometal surface energy transfer (NSET) between them both, which are constructed for prostate specific antigen (PSA) assay. Taking advantage of the networked nanostructure of aptamer–QDs/NFs, the fluorescent film can detect PSA with high sensitivity and a detection limit of 0.46 pg mL −1, which was further applied in real clinical serum samples. Coupling the surface grafted techniques to the advanced network nanostructure of electrospun NFs, the proposed aptasensing platform can be easily extended to achieve sensitive and selective assays for other biomarkers.